(untitled) (Research, Society and Development, 2020)
This article aims to compare the conception of human nature according to Notonagoro and Drijarkara and their implications for the development of the philosophy of Pancasila. For this reason, this study uses a comparison method. With the basic understanding of Pancasila is a philosophical system and human as its ontological basis, the philosophy of Pancasila can be well understood through an understanding of human nature. Therefore, the understanding of Pancasila must begin with understanding of human nature. This study found that Notonagoro and Drijarkara had similarities and differences in formulating human nature as ontological basis of Pancasila. Equally, both see humans not as a single entity. Notonagoro sees humans as monopluralists, while Drijarkara sees humans as singular (kedwitunggalan). However, both have differences in the things emphasized. Notonagoro emphasizes human nature as monopluralis, while Drijarkara as persona. As monopluralis, a good human is one who has pious character, while as persona, human perfection is achieved through his relationship with others in love. This difference has implications in developing the philosophy of Pancasila. Notonagoro sees human nature that can be understood in the nature of the precepts of Pancasila, while Drijarkara sees Pancasila as the actualization of an existential human actualization.